Synergistic anti‐pancreatic cancer immunological effects by treatment with reduced expression in immortalized cells/dickkopf‐3 protein and peripheral blood mononuclear cells. Issue 6 (June 2016) - Uchida, Daisuke; Shiraha, Hidenori; Kato, Hironari; Sawahara, Hiroaki; Nagahara, Teruya; Iwamuro, Masaya; Kataoka, Junro; Horiguchi, Shigeru; Watanabe, Masami; Takaki, Akinobu; Nouso, Kazuhiro; Nasu, Yasutomo; et al.
Abstract: Background and Aim: Reduced expression in immortalized cells/dickkopf‐3 (REIC/DKK3) is a reported tumor suppressor gene and has potential to become an innovative therapy for various cancers. We examined the antitumor immunological effects of human REIC/DKK3 protein against pancreatic cancer. Methods: Activation of extracellular signal‐regulated kinases 1 and 2, mammalian target of rapamycin, and signal transducer and activator of transcription 3 by REIC/DKK3 protein was assessed in human peripheral blood mononuclear cells using immunoblotting. Pancreatic cancer cell lines (AsPC‐1 and MIA Paca‐2) were cocultured with peripheral blood mononuclear cells, and the anticancer effects of REIC/DKK3 protein were assessed using the methyl thiazole tetrazolium, cytotoxicity, and enzyme‐linked immunospot assays. The antitumor immunological effects of the combined treatment with REIC/DKK3 protein and peripheral blood mononuclear cells were also assessed in a pancreatic cancer model using non‐obese diabetic/severe combined immunodeficiency mice. Results: The REIC/DKK3 protein activated extracellular signal‐regulated kinases 1 and 2, mammalian target of rapamycin, and signal transducer and activator of transcription 3 in peripheral blood mononuclear cells. REIC/DKK3 protein inhibited in vitro cancer cell viability and enhanced cytotoxicity when incubated with peripheral blood mononuclear cells. REIC/DKK3 protein induced significant production of interferon gamma from lymphocytes incubated with pancreatic cancer cells, indicating that CD8+ T cells were activated in the peripheral blood mononuclear cells when cocultured with AsPC‐1 and MIA Paca‐2 in the presence of REIC/DKK3 protein. Combined treatment with REIC/DKK3 protein and peripheral blood mononuclear cells produced in vivo anticancer immunostimulatory effects on pancreatic cancer cells. Conclusions: The REIC/DKK3 protein and peripheral blood mononuclear cells synergistically enhanced anticancer immunological effects against pancreatic cancer cells. The observed immunomodulatory effect of combined treatment likely occurs in adenovirus‐mediated REIC/DKK3 gene therapy and provides important clues to the therapeutic mechanisms involving immune cells.